An Analysis Of Blockchain Fundamentals, Technical, And Macroeconomic Factors On Bitcoin Price - Ahmad Yani; Septiana Sihombing; Yogi Cahyo Ginanjar (Integrated Journal of Business and Economics (IJBE), 2026)
Bitcoin has emerged as a prominent digital asset that blends financial innovation, technological advancement, and speculative behavior. However, its growing adoption raises sustainability concerns due to energy-intensive mining and environmental impacts. This study investigates the determinants of Bitcoin prices within the framework of sustainable digital finance by integrating blockchain fundamentals, technical indicators, and macroeconomic variables. Using daily data from 24 November 2021 to 21 November 2024 (753 observations), the analysis conducted with Stata 16—examines miners’ revenue, hashrate, transactions per block, unique addresses, mining difficulty, and trade volume as internal factors, along with gold prices, WTI crude oil, and the S&P 500 index as external factors. Results show that miners’ revenue, hashrate, and transactions per block have positive and significant effects on Bitcoin prices, emphasizing the importance of mining performance and network activity. Trade volume and unique addresses also display positive but less consistent influences, while mining difficulty remains statistically insignificant. Among external factors, WTI crude oil significantly affects Bitcoin prices. Overall, findings suggest that Bitcoin operates as both a financial asset and a technology-driven ecosystem shaped by blockchain dynamics and macroeconomic conditions. The study highlights the need for sustainable mining practices and transparent regulatory frameworks to enhance environmental efficiency.